A Transcriptomics and Comparative Genomics Analysis Reveals Gene Families with a Role in Body Plan Complexity - Kramer, Eric M.; Li, Wanying (Frontiers in Plant Science, 2017)
We analyzed tissue-specific transcriptomes of Arabidopsis thaliana and identified 66 gene families with a high frequency of “gradient genes” - genes showing a significant expression gradient between tissues. Gradient gene families include many with roles in hormone and peptide signaling, cell wall synthesis and remodeling, secondary metabolism, transcriptional regulation, and transport between cells. We compared the size of the gradient gene families among the genomes of four plant species with radically different body plans – a single-celled algae, a moss, a eudicot, and a monocot – and found that most of the gradient gene families (58/66) expanded in parallel with the evolution of morphological complexity. A novel measure of tissue diversity was used to show that members of any one gradient gene family tend not to be clustered in a single tissue, but are rather apportioned evenly across the tissues studied. Considered together, our results suggest that the diversification of these gene families supported the diversification of tissue types and the evolution of body plan complexity in plants.